A 5-GHz direct-conversion CMOS transceiver. - Pengfei Zhang (IEEE Journal of solid state circuits)
A CMOS transceiver fully compliant with IEEE 802.11a in the unlicensed national information infrastructure (UNII) band (5.15-5.35 GHz) achieves a receiver sensitivity of -5 dBm for 64-QAM (quadrature amplitude modulation) with an error vector magnitude (EVM) of -29.3 dB. A single-sideband mixing technique for local-oscillator signal generation avoids frequency pulling. Realized in 0.18-μm CMOS and operating from 1.8-V power supply, the design consumes 171 mW in receive mode and 135 mW in transmit mode while occupying less than 13 mm2.